Hydrophobic liquid-infused porous polymer surfaces for antibacterial applications - Li, Junsheng; Kleintschek, Tanja; Rieder, Annika; Cheng, Yin; Baumbach, Tilo; Obst, Ursula; Schwartz, Thomas; Levkin, Pavel (ACS applied materials & interfaces, 2013)
Biofilms represent a fundamental problem in environmental biology, water technology, food hygiene as well as in medical and technical systems. Recently introduced slippery liquid-infused porous surface (SLIPS) showed great promise for preventing biofilm formation owing to the low surface energy of such surface in combination with its self-cleaning properties. In this study we demonstrated a novel hydrophobic liquid-infused porous poly(butyl methacrylate-co-ethylene dimethacrylate) surface (slippery BMA-EDMA) with bacteria-resistance in BM2 mineral medium and long-term stability in aqueous environments. We showed that the slippery BMA-EDMA surface prevents biofilm formation of different strains of opportunistic pathogen Pseudomonas aeruginosa for at least up to 7 days in low nutrient medium. Only ∼1.8% of the slippery surface was covered by the environmental P. aeruginosa PA49 strain under investigation. In uncoated glass controls the coverage of surfaces reached ∼55% under the same conditions. However, in high nutrient medium, more relevant to physiological conditions, the biofilm formation on the slippery surface turned out to be highly dependent on the bacterial strain. Although the slippery surface could prevent biofilm formation of most of the P. aeruginosa strains tested (∼1% surface coverage), the multiresistant P. aeruginosa strain isolated from wastewater was able to cover up to 12% of the surface during 7 days of incubation. RAPD-PCR analysis of the used P. aeruginosa strains demonstrated their high genome variability, which might be responsible for their difference in biofilm formation on the slippery BMA-EDMA surface. The results show that although the slippery BMA-EDMA surface has a great potential against biofilm formation, the generality of its bacteria resistant properties is still to be improved.